Bent-to-planar Si-rhodamines: a distinct rehybridization lights up NIR-II fluorescence for tracking nitric oxide in the Alzheimer's disease brain. Issue 15 (27th March 2023) - Xu, Qingshuang; Zhang, Yutao; Zhu, Mingming; Yan, Chenxu; Mao, Wenle; Zhu, Wei-Hong; Guo, Zhiqian
Abstract : We report a configuration-dependent strategy to construct bent-to-planar NIR-II fluorophores, based on an innovative rehybridization fluorogenic building block, showing promise for illuminating biological events with high spatio-temporal resolutions. Abstract : An ongoing revolution in fluorescence-based technologies has transformed the way we visualize and manipulate biological events. An enduring goal in this field is to explore high-performance fluorogenic scaffolds that show tunability and capability for in vivo analysis, especially for small-molecular near-infrared (NIR) fluorophores. We present a unique bent-to-planar rehybridization design strategy for NIR fluorogenic scaffolds, thus yielding a palette of switchable bent/planar Si-rhodamines that span from visible to NIR-II wavelengths. We demonstrate that the rehybridization of meso -nitrogen in this innovative NIR scaffold Cl-SiRhd results in flipping between the disruption and recovery of the polymethine π-electron system, thereby significantly altering the spectral wavelength with crosstalk-free responses. Using elaborately lighting-up NIR-II probes with ultra-large Stokes shifts ( ca. 250 nm), we successfully achieve real-time in situ monitoring of biological events in live cells, zebrafish, and mice. Notably, for the first time, the light-up NIR-II probe makes a breakthrough in directly in situ tracking nitric oxide (NO) fluctuations in the brains of mice with Alzheimer's disease. This de novo bent-to-planar rehybridization strategy of NIR-II probes opens up exciting opportunities for expanding the in vivo imaging toolbox in both life science research and clinical applications.